Manhaj Imam Ibn Furak dalam berinteraksi dengan hadith sifat khabariyyah - Nik Muhammad Abdul Hayyi Nik Idris; Umar Muhammad Noor; Rahim Kamarul Zaman (Kolej Universiti Islam Antarabangsa Selangor, 2024)
Ibn Fūrak was one of the most influential hadith scholars in the fourth century. His prominence in the field of hadith can be seen through his masterpieces, including Mushkil al-Hadīth. This book contains the description and point of view of Imam Ibn Furak on the hadiths of khabariyyah attributes and their explanations. This study is essential in analysing Imam Ibn Furak's facts on the meaning of hadiths of khabariyyah attributes due to his expertise in various disciplines. By observing the khabariyyah attributes of hadiths from the correct perspective, the general public will gain accurate knowledge that aligns with the wishes of the nuṣūṣ (textual) and the beliefs of the salaf. This study aims to identify Imam Ibn Furak's view on hadith khabariyyah attributes based on the content of the book Mushkil al-Hadīth. Next, the study formulates the concept of understanding and interacting with khabariyyah attributes hadiths according to the beliefs of the Salaf. This study applies the inductive method to obtain hadiths related to the description of the Salaf in the book Mushkil al-Hadīth. Descriptive methods are carried out to describe and summarise Imam Ibn Furak's statement regarding the concept of interacting with khabariyyah attributes hadiths. The study's findings show that Imam Ibn Furak has explained the correct description of interacting with the hadiths of khabariyyah attributes and dispelled any accusation that he used the forbidden knowledge of kalam. In addition, he often discusses Arabic language debates in the book Mushkil al-Hadīth. Overall, khabariyyah attributes hadiths not only need to be confirmed to be authentic, but they also need to be based on the understanding of the Salaf that is in line with the guidance of the sunnah.